2009
DOI: 10.1128/aem.01821-08
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Escherichia coli Isolates from Swine and Wild Small Mammals in the Proximity of Swine Farms and in Natural Environments in Ontario, Canada

Abstract: Wild animals not normally exposed to antimicrobial agents can acquire antimicrobial agent-resistant bacteria through contact with humans and domestic animals and through the environment. In this study we assessed the frequency of antimicrobial resistance in generic Escherichia coli isolates from wild small mammals (mice, voles, and shrews) and the effect of their habitat (farm or natural area) on antimicrobial resistance. Additionally, we compared the types and frequency of antimicrobial resistance in E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

25
159
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(188 citation statements)
references
References 38 publications
25
159
3
1
Order By: Relevance
“…The percentage of wild mice with antimicrobial-resistant E. coli isolates in this investigation (3.7%, 3/81) was as low as that among small wild mammals living in natural areas (10%, 2/20) [10]. It has been reported that the proximity of wild animals to human settlements and the livestock industry increases antimicrobial-resistance among E. coli isolates from wild animals [7,10].…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…The percentage of wild mice with antimicrobial-resistant E. coli isolates in this investigation (3.7%, 3/81) was as low as that among small wild mammals living in natural areas (10%, 2/20) [10]. It has been reported that the proximity of wild animals to human settlements and the livestock industry increases antimicrobial-resistance among E. coli isolates from wild animals [7,10].…”
mentioning
confidence: 89%
“…The usage of antimicrobial agents is considered the most important factor in the selection and dissemination of antimicrobial-resistant bacteria. Although antimicrobial agents are not generally administered to wild animals, the prevalence of antimicrobial-resistant Escherichia coli isolates was determined in some wild animals [4,5,7,10,12,13]. The source of antimicrobial-resistant bacteria among wild animals is still debatable.…”
mentioning
confidence: 99%
See 3 more Smart Citations